2017
DOI: 10.1016/j.juro.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness Criteria for Active Surveillance of Prostate Cancer

Abstract: By virtue of this work urologists have the opportunity to present specific recommendations from the panel to their individual patients. Community-wide efforts aimed at increasing rates of active surveillance and reducing practice and physician level variation in the choice of active surveillance vs treatment are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…23,24 While these tools more accurately characterize risk for individual patients, they are still limited by the lack of biological M A N U S C R I P T of an individual core on surveillance. 5 In this study we sought to determine if this hesitance is rationally based, by using OncotypeDx Prostate to measure biologic potential (as measured by GPS and the estimation of LFP) of GrdGrp 1 tumors as a function of tumor volume. We found that OncotypeDx Prostate performed similarly in our cohort as in other reported series, with reclassification rates of 6.3% for NCCN VLR to LR, 7.2% of LR to IR, and 43% LR to VLR in our study compared to published rates of 6-9% 10-11%, and 33-51%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 While these tools more accurately characterize risk for individual patients, they are still limited by the lack of biological M A N U S C R I P T of an individual core on surveillance. 5 In this study we sought to determine if this hesitance is rationally based, by using OncotypeDx Prostate to measure biologic potential (as measured by GPS and the estimation of LFP) of GrdGrp 1 tumors as a function of tumor volume. We found that OncotypeDx Prostate performed similarly in our cohort as in other reported series, with reclassification rates of 6.3% for NCCN VLR to LR, 7.2% of LR to IR, and 43% LR to VLR in our study compared to published rates of 6-9% 10-11%, and 33-51%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 Furthermore, despite long term evidence of the safety of active surveillance for most men with pure grade group (GrdGrp) 1 (i.e., Gleason score 3+3) tumors, 3,4 violation of the Epstein criteria based on tumor volume is used to exclude men against the recommendation for surveillance in some provider/institutional protocols. 5 The diagnostic inaccuracies of biopsy and traditional risk stratification measures create a need for improved methods to identify men at low risk of progression who may avoid initial therapy, a limitation that is being addressed by the growing use of genomic biomarkers [6][7][8] and multiparametic magnetic resonance imaging as diagnostic tools. 9,10 The OncotypeDX Genomic Prostate Score (GPS) TM , is a 17-gene quantitative RT PCR assay of selected genes from four cancer related molecular pathways (androgen signaling, cellular organization, stromal response, and cellular proliferation) 11 that has been analytically 11 and clinically 12,13 validated when measured on prostate biopsies to predict the presence of adverse pathology (GrdGrp 3 or higher or non-organ confined disease), as well as time to biochemical recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Our nding that physicians perceive rapidly evolving and non-standardized follow-up protocols as a barrier to the adoption of AS has also been reported previously [54]. Research is underway to clarify biopsy and surveillance protocols, which may reduce uncertainty in selecting and following patients on AS [5,[55][56][57], particularly for young men [55]. Prospective research on appropriate recommendations for patients who are at higher risk for prostate cancer death, such as African American men, also may be warranted.…”
Section: Discussionmentioning
confidence: 70%
“…The result is the new lower risk Gleason score 6 cancer. This and several genomic tests have made it easier to identify patients who are good candidates for active surveillance …”
mentioning
confidence: 99%
“…This and several genomic tests have made it easier to identify patients who are good candidates for active surveillance. 12 Recommendations of the American Urological Association, the American Society of Therapeutic Radiation Oncology, the Society of Urologic Oncology, and American Society of Clinical Oncology now clearly state that active surveillance is the preferred management strategy for most men with low-risk disease. 12 Today, about one-half of men with newly diagnosed, localized disease enter active surveillance protocols.…”
mentioning
confidence: 99%